Ranking Cognitive Flexibility in a Group Setting of Rhesus Monkeys with a Set-Shifting Procedure - Shnitko, Tatiana A.; Allen, Daicia C.; Gonzales, Steven W.; Walter, Nicole A. R.; Grant, Kathleen A. (Frontiers in Behavioral Neuroscience, 2017)
Attentional set-shifting ability is an executive function underling cognitive flexibility in humans and animals. In humans, this function is typically observed during a single experimental session where dimensions of playing cards are used to measure flexibility in the face of changing rules for reinforcement (i.e., the Wisconsin Card Sorting Test (WCST)). In laboratory animals, particularly non-human primates, variants of the WCST involve extensive training and testing on a series of dimensional discriminations, usually in social isolation. In the present study, a novel experimental approach was used to assess attentional set-shifting simultaneously in twelve rhesus monkeys. Specifically, monkeys living in individual cages but in the same room were trained at the same time each day in a set-shifting task in the same housing environment. As opposed to the previous studies, each daily session began with a simple single-dimension discrimination regardless of the animal’s performance on the previous session. A total of 8 increasingly difficult, discriminations (sets) were possible in each daily 45 minute session. Correct responses were reinforced under a second-order schedule of flavored food pellet delivery, and criteria for completing a set was 12 correct trials out of a running total of 15 trials. Monkeys progressed through the sets at their own pace and abilities. The results demonstrate that all 12 monkeys acquired the simple discrimination (the first set), but individual differences in the ability to progress through all 8 sets were apparent. A performance index that encompassed progression through the sets, errors and session duration was calculated and used to rank each monkey’s performance in relation to each other. Overall, this version of a set-shifting task results in an efficient assessment of reliable differences in cognitive flexibility in a group of monkeys.